Regional differences in the patient population of general practices in northern Germany: results of a mixed-methods study - Martin Scherer; Ingmar Schäfer; Dagmar Lühmann; Heike Hansen; Nadine Janis Pohontsch; Agata Kazek; Hanna Hardt (BMJ Open)
Objectives The aim of our study was to explore patient types in general practitioner (GP) practices and to quantify the regional differences of the frequencies of these patient types in northern Germany.Design and setting We conducted a mixed-methods study based on focus groups and standardised interviews with GPs. All counties and independent cities within a radius of 120 km around Hamburg were assigned one of three regional categories (urban areas, environs, rural areas). The focus groups were analysed using qualitative content analysis. Relative frequencies of consultations by patient types and differences between the regions were calculated. Logistic regression analyses were used to identify differences among regions.Participants Nine focus groups with 65 GPs (67.7% male). From the 280 initially recruited GPs 211 (65.4% male) could be personally interviewed.Results Four themes with 27 patient types were derived from the focus groups: patients classified by morbidity, sociodemographic characteristics, special care needs and patient behaviour. Five patient characteristics were significantly more prevalent in urban areas than rural areas: patients with migration background and culturally different disease concepts (OR 1.23; 95% CI 1.06 to 1.42), privately insured patients (OR 1.17; 95% CI 1.05 to 1.31), educationally disadvantaged patients with low health literacy (OR 1.11; 95% CI 1.04 to 1.19), patients with psychiatric disorders (OR 1.07; 95% CI 1.02 to 1.12) and senior citizens living on their own without caregivers (OR 1.05; 95% CI 1.05 to 1.31). Three patient types were significantly less prevalent in urban areas: minors accompanied by their parents (OR 0.71; 95% CI 0.61 to 0.83), patients with poor therapy adherence (OR 0.87, 95% CI 0.80 to 0.95) and patients with dementia (OR 0.90; 95% CI 0.82 to 0.99).Conclusions GPs could compensate the specific needs of their patients with medical training aligned with the requirements of their region. Urban GPs need skills treating patients with psychiatric, social and cultural problems, rural GPs regarding the care for children or noncompliant patients.Trial registration number NCT02558322